2021
DOI: 10.21744/lingcure.v5ns3.1840
|View full text |Cite
|
Sign up to set email alerts
|

analysis model of impolite Indonesian language use

Abstract: This research was based on the reality of the use of Indonesian language on social media that was vulgar, destructive, full of blasphemy, scorn, sarcasm, and tended to be provocative. This condition has destructive power because it spreads very quickly and is capable of arousing very strong emotions. This article aimed at presenting the results of research on the analysis model of impolite Indonesian language use. This model was developed from tracing status on social media which included language impoliteness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, the current study showed that Indonesian netizens tended to use offensive language that is intended to mock, insult, or even ridicule others. This can be in cultural and religious contexts, as the Indonesian language on social media is full of offensive language and tends to be provocative (Anwar et al, 2021). Both cultural and religious contexts have quite distinct perspectives on offensive language and can have very varied effects on online social interactions that can lead to blasphemy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the current study showed that Indonesian netizens tended to use offensive language that is intended to mock, insult, or even ridicule others. This can be in cultural and religious contexts, as the Indonesian language on social media is full of offensive language and tends to be provocative (Anwar et al, 2021). Both cultural and religious contexts have quite distinct perspectives on offensive language and can have very varied effects on online social interactions that can lead to blasphemy.…”
Section: Discussionmentioning
confidence: 99%
“…Competition and selection of different language units from the "feature pool" are inherent in dynamics of language evolution. In light of this, ecolinguistic approach to allonymy is employed to trace competition and selection of such lexical units in the process of Caribbean English development into a regional variety (Anwar et al, 2021;Karamoy et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, research regarding the application of language politeness to students in interactions with lecturers is a very relevant aspect and needs to be explored further. This will help improve the understanding and practice of language politeness among students, which in turn will enrich the learning experience and form a generation that is able to communicate effectively and appreciate every interaction in the academic environment (anwar et al, 2021;Kartika, 2016).…”
Section: Introductionmentioning
confidence: 99%